Representations of the Orlicz Figà-Talamanca Herz algebras and Spectral Subspaces - Lal, Rattan; Kumar, N. Sh. (Methods of Functional Analysis and Topology, 2020)
Let G be a locally compact group. In this note, we characterise non-degenerate *-representations of A_Φ(G) and B_Φ(G). We also study spectral subspaces associated to a non-degenerate Banach space representation of A_Φ(G).